The Death of Methods ("nouvelles vagues") in the Teaching of Language(s) - Miranda Esquerre, Luis (2010)
The use of a particular method has been and is regarded as the solution for all or at least the major problems in the teaching of the first or the one (s) second (s) language (s). However, in practice, one can say that we all have failed in some way, so much so that now there is talk of "the death of methodologies."